Analisis Kecepatan Angin Di Industri Pengolahan Kayu - Rodesia Mustika Rozi; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
wood processing company that manufactures pallets in its operational activities has the potential to generate noise coming. Which in the production process produces noise from the use of machines. Noise arising from the use of machines can affect the health and comfort of workers, especially in hearing loss. The purpose of this research is to know the intensity of noise resulting from the use of machines, noise mapping, evaluation of noise intensity, exposure time and noise control efforts. In this research measurements of temperature, wind speed and noise intensity using a Sound Level Meter (SLM). The results of this research found that the highest wind speed reached 1,2 m/s and the lowest wind speed 0 m/s Keywords: Wind Speed, Wood Processing Company, Noise